Leksikon-leksikon Bermakna ‘Makan’ dalam Bahasa Jawa Dialek Banyumas - Suyanto Suyanto; Sri Puji Astuti (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
This study aims (1) to identify lexicon forms in BJDB meaning ‘to eat’; (2) explain the cultural meaning of lexicons in Javanese of Banyumas Dialect (JoBD/BJDB) which means ‘to eat’; and (3) explain that cultural reflection in the JoBD lexicon means ‘eating’. This study uses Duranti’s anthropolinguistic theoretical framework with its three main concepts, performance, indexiciality, and participation. Study design uses case study. Collecting data using observation and in-depth interviews. Data analysis was carried out in stages: description, analysis, and interpretation of data. The study findings show that the lexicons in JoBD that mean ‘to eat’ are mangan, madhang, maem, nedhi / nedha, dhahar, badhog / nyekek, leg / gaglag / untal, kedhapi, and mayoran. The use of the lexicon which means ‘to eat’ in JoBD is quite varied depending on the context of use (participants and real usage / situation). The neutral nuanced lexicon of JoBD means 'to eat' is: mangan and madang which are used in the environment of family, friends or neighbors of equal socioeconomic status. Finely nuanced lexicon is nedhi / nedha and maem used by parents (mother) to her sons and daughters. The lexicon of high value is the dhahar used by O1 against the respected O2. Lexicon means ‘eat’ typical for lower socioeconomic class is badhog, nyekek, leg, gaglag, untal often used to express anger, annoyance and ngluloke. Mayoran is a lexicon means 'party' among close friends or extended family.